Rights of patient and the disabled - Montemayor, Jose C. Jr. (Quezon City, Philippines : Central Book Supply, 2023)
Other barriers include: internalized barriers (Low expectations of patients and people with disabilities can undermine their confidence and aspirations. Disability rights is complex because there are multiple ways in which a person with a disability can have their rights violated in different socio-political, cultural, and legal contexts. For example, in modern times, a common barrier that individuals with disabilities face deals with employment. Specifically, employers are often unwilling or unable to provide the necessary accommodations to enable individuals with disabilities to effectively carry out their job functions.
Includes bibliographical references.
Keywords: PEOPLE WITH DISABILITIES -- LEGAL STATUS, LAW ETC -- PHILIPPINES